The Main Determinants for Suicidal Ideation in a Romanian Cohort of Multiple Sclerosis Patients - Andreea Romaniuc; Rodica Bălaşa; Nicoleta Ştirbu; Smaranda Maier; Sebastian Andone; Zoltan Bajko; Laura Bărcuţean; Septimiu Voidăzan; Anca Moţăţăianu (Behavioural Neurology)
Objective. To determine the prevalence of suicidal concerns (SC) in a large multiple sclerosis (MS) patient group and to assess the major determinants that are implicated in their occurrence. Methods. A total of 349 patients were included in the study. They completed a survey about their demographic characteristics, psycho-socio-economic data, and disease-related information. Their disability level was assessed using the Expanded Disability Status Scale (EDSS) based on the neurological examination performed by the same doctor for every patient and the SC were documented with the Beck Depression Inventory-II questionnaire. Results. The study included 112 men and 237 women, with a mean age around 42 years old. Suicidal thoughts were more frequent in men, while suicidal intentions in women. Positive correlations were found between SC and depression, EDSS, total number of relapses, disease duration, and level of education. From the EDSS functional scores, only the pyramidal score and the cerebellar score presented a significant correlation with SC. None of the patients with clinically isolated syndrome had SC. The type of disease-modifying therapy, marital and occupational status, and the presence of children did not influence the presence of SC. Conclusions. The prevalence of SC is higher in patients with MS compared to the general population. Their occurrence is mostly influenced by the disease itself (duration, relapses, acquired disability) and also by depression and lack of education.